Ride the pink horse [videorecording (DVD)] - Montgomery, Robert, 1904-1981; Hecht, Ben, 1894-1964; Lederer, Charles, 1910-1976; Hendrix, Wanda, 1928-1981; King, Andrea, 1919-2003; Gomez, Thomas, 1905-1971; Clark, Fred, 1914-1968; Smith, Art, 1899-1973; Gaines, Richard, 1904-1975; Conde, Rita, 1914-1989; Flores, Iris; Renaldo, Tito; et al. (Criterion collection ;, 2015)
A tough-talking former GI comes to a small New Mexico town to shake down a gangster who killed his best friend; events turn out neither as planned nor at all well.